IFI16, a nuclear innate immune DNA sensor, mediates epigenetic silencing of herpesvirus genomes by its association with H3K9 methyltransferases SUV39H1 and GLP - Arunava Roy; Anandita Ghosh; Binod Kumar; Bala Chandran (eLife, 2019)
IFI16, an innate immune DNA sensor, recognizes the nuclear episomal herpes viral genomes and induces the inflammasome and interferon-β responses. IFI16 also regulates cellular transcription and act as a DNA virus restriction factor. IFI16 knockdown disrupted the latency of Kaposi’s sarcoma associated herpesvirus (KSHV) and induced lytic transcripts. However, the mechanism of IFI16’s transcription regulation is unknown. Here, we show that IFI16 is in complex with the H3K9 methyltransferase SUV39H1 and GLP and recruits them to the KSHV genome during de novo infection and latency. The resulting depositions of H3K9me2/me3 serve as a docking site for the heterochromatin-inducing HP1α protein leading into the IFI16-dependent epigenetic modifications and silencing of KSHV lytic genes. These studies suggest that IFI16’s interaction with H3K9MTases is one of the potential mechanisms by which IFI16 regulates transcription and establish an important paradigm of an innate immune sensor’s involvement in epigenetic silencing of foreign DNA.